Profitabilitas Terhadap Harga Saham Perusahaan Sektor Industri Dasar Dan Kimia - Septianti, Ajeng; Yudhawati, Diah; Supramono, Supramono (Manager : Jurnal Ilmu Manajemen, 2019)
The purpose of this research is to analyze the influence of Return On Equity (ROE), Net Profit Margin (NPM) to stock price in 2011-2017. This study uses secondary data, the sample in this study as many as 28 data derived from livestock feed companies listed on the Indonesia Stock Exchange from 2011 to 2017 and include complete financial report data. Sampling technique using purposive sampling technique or sampling based on certain considerations and criteria. The analytical method used is simple linear regression analysis and multiple linear regression analysis with first classical asusmsi test which includes normality test, heteroscedasticity test, autocorrelation test. The results of this study show that partially Return On Equity (ROE) has a positive and insignificant effect on price, Net Profit Margin (NPM) has a positive and insignificant effect on stock prices. Simultaneously Return On Equity (ROE) and Net Profit Margin (NPM) have positive and insignificant effect to stock price at company of basic industry and kumia subs of poultry feed listed on Indonesia Stock Exchange (BEI) year 2011- 2017.